Impact of autophagic regulation on splenic red pulp macrophages during cerebral malarial infection. (August 2019) - Sengupta, Anirban; Sarkar, Samrat; Keswani, Tarun; Mukherjee, Saikat; Ghosh, Soubhik; Bhattacharyya, Arindam
Abstract: Splenic red pulp macrophages play a critical role infiltration of infected RBC and elimination of pathogens during malarial infection. However, the efficiency of pathogenic processing and the intricate pathway followed by them to boost the downstream immune response has not been studied in details. We checked the status of autophagic regulation within the cells both before and after the infection and also modulated the autophagic flux with either its inducer or inhibitor. We found that the upregulation of autophagic gene and the corresponding pathway is correlated with better parasite clearance and survivability, with an enhanced downstream immune response. It also increases their phagocytic potential with better Lysosomal associated protein I and II synthesis. The autophagolysosome formation increases as well, and more vacuole bound LC3B protein are detected. Chemokine synthesized from Red Pulp macrophage helps in mediating the induction for recruiting neutrophil and CD4 + T cells to the splenic red pulp region. The skewing of M1 macrophage polarity is observed post autophagic induction with a better costimulatory molecule like CD80, CD86 expression and antigen presenting molecule MHC I, MHC II is observed. This study shows the possibility of an alternative or adjuvant therapy regimen for the malarial patient by inducing the autophagic pathway that targets the red pulp macrophages. This might be helpful for better pathogen degradation and processing. The subsequent clearance of parasite will result in a better outcome for the patients. Graphical abstract: Unlabelled Image Highlights: Autophagy induced red pulp macrophages activate parasite clearance and enhances survivability in cerebral malaria. Antigen processing and presentation, co-stimulation activity elicited post autophagic induction. Induction of chemokine signal for Neutrophil and CD4T cells Infiltration within splenic red pulp zone generated from RPM.